The Effect of Using S.A.M.R Model in Learning Trapping In Soccer for 2nd Grade Secondary School Students - Redha, Jafar; Habeeb, Maythem (Journal of Physical Education, 2020)
The research aimed to using Substitution, Augmentation, Modification and Redefinition Model S.A.M.R. on learning. The researchers used the experimental method on 2nd grade secondary school students from 3rd Al Kurk / ministry of education. The program was applied for 3 weeks with two sessions per week to conclude that using SAMR model facilitates learning. The results showed significant differences between pre and posttests results in favor of the experimental group in learning soccer trapping finally the researchers recommended using this model for learning other soccer skills.